2010
DOI: 10.1111/j.1469-8749.2010.03686.x
|View full text |Cite
|
Sign up to set email alerts
|

Gross muscle morphology and structure in spastic cerebral palsy: a systematic review

Abstract: PCSA Physiological cross-sectional area AIM This systematic review and critical evaluation of the literature was conducted to determine how gross muscle morphology and structure are altered in individuals with spastic cerebral palsy (CP).METHOD Electronic databases were searched for articles describing studies of muscle morphological and structural properties in individuals with spastic CP. Data describing muscle fascicle length, belly length, fascicle angle, cross-sectional area, volume, and thickness were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
229
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(240 citation statements)
references
References 68 publications
(301 reference statements)
7
229
2
2
Order By: Relevance
“…A recent systematic review [20] concluded, on the basis of cross-sectional studies, that there was consistent evidence for reduced calf muscle size in the paretic limb in spastic CP compared to typically developing (TD) peers [21][22][23][24][25]. Barber et al [26] subsequently showed that medial gastrocnemius (MG) muscle physiological crosssectional area (PCSA), but not fascicle length, was reduced by 27 % in children aged 2-5 years with spastic CP who had not commenced BoNT-A treatment compared to TD peers.…”
mentioning
confidence: 99%
“…A recent systematic review [20] concluded, on the basis of cross-sectional studies, that there was consistent evidence for reduced calf muscle size in the paretic limb in spastic CP compared to typically developing (TD) peers [21][22][23][24][25]. Barber et al [26] subsequently showed that medial gastrocnemius (MG) muscle physiological crosssectional area (PCSA), but not fascicle length, was reduced by 27 % in children aged 2-5 years with spastic CP who had not commenced BoNT-A treatment compared to TD peers.…”
mentioning
confidence: 99%
“…21,22 Children with CP have been shown to have smaller and weaker muscles. 23 Over the last decade, weakness has been increasingly recognised as a significant motor impairment, [22][23][24] purportedly affecting functional ability in children with CP. 25,26 A recent review of the literature on spastic CP found consistent evidence for small muscle size as indicated by reduced muscle volume, crosssectional area, thickness, and belly length in comparisons of paretic muscles with non-paretic and typically developing muscles.…”
mentioning
confidence: 99%
“…25,26 A recent review of the literature on spastic CP found consistent evidence for small muscle size as indicated by reduced muscle volume, crosssectional area, thickness, and belly length in comparisons of paretic muscles with non-paretic and typically developing muscles. 24 Barber et al 25 described volumetric deficits of 22% in the medial gastrocnemii of young children (2-5y) with spastic CP compared with typically developing children. For a population already predisposed to decrements in muscle size and strength, a treatment that potentially leads to further atrophy and weakening of the muscle should be well understood.…”
mentioning
confidence: 99%
“…Both are responsible for increasing lactic acid production, use of muscle glycogen, pain, and functional limitation characterized as an inability to perform motor tasks [4][5][6].…”
Section: Introductionmentioning
confidence: 99%